DAMPAK GREEN BANKING DISCLOSURE DAN CORPORATE RISK DISCLOSURE TERHADAP NILAI PERUSAHAAN: BUKTI EMPIRIS DARI BANK UMUM SYARIAH - Claduri, Riskadani Dea; Rahayu, Sri; Lubis, Farida Khairani (Universitas Dharmawangsa, 2025)
This study aims to examine the impact of Green Banking Disclosure and Corporate Risk Disclosure on firm value in Islamic Commercial Banks in Indonesia. Using a quantitative approach, this research relies on secondary data from the annual and sustainability reports of 12 Islamic banks over the 2021–2023 period. The sample was selected using purposive sampling, and data analysis was conducted through multiple linear regression using SPSS software. The results show that Green Banking Disclosure has a positive effect on Return on Equity (ROE), indicating that the more transparent a bank is in disclosing its environmentally friendly policies, the better its financial performance. In contrast, Corporate Risk Disclosure negatively affects Return of Equity (ROE), suggesting that greater risk disclosure may lead investors to be more cautious in assessing the company. Overall, both variables significantly influence firm value. This study provides insights for Islamic banks to enhance transparency in disclosing environmental and corporate risk-related information, as it can impact investor perceptions and market valuation.